2013
DOI: 10.1063/1.4817655
|View full text |Cite
|
Sign up to set email alerts
|

The thermoelastic bending and thermal diffusion processes influence on photoacoustic signal generation using open photoacoustic cell technique

Abstract: Thermal diffusion and thermoelastic bending are two consequences of heating generated on the sample surface. Both are employed in Open Photoacoustic Cell (OPC) technique to measure the thermal diffusivity of the sample. In this work, we explore the potential use of the OPC technique to study the effectiveness of thermoelastic bending process and thermal diffusion process on photoacoustic signal (S) generation in solids. More specifically, it is observed that if the thermoelastic bending process becomes more ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…when the ideal thermally thick sample condition, f >>fc, is fulfilled), αT=a1+a2 takes a value of (1.9±0.6)×10 -5 °K -1 (black circle in the figure), which is in agreement with the value reported for the linear thermal expansion coefficient of stainless steel. Thus, for measurement of this parameter with accuracy an adequate method should involve measurements for different material thicknesses following the above methodology.The above result confirms that of a previous reported work of Somer et al17 , where it was demonstrated that in the so-called Open Photoacoustic Cell (OPC) set-up, the actual value of the thermoelastic bending parameter (determined by the sample´s thermal expansion coefficient) approaches a constant value as the sample thickness becomes thicker, i.e. as the sample goes towards the ideal thermally thick regime (see Fig.…”
supporting
confidence: 93%
“…when the ideal thermally thick sample condition, f >>fc, is fulfilled), αT=a1+a2 takes a value of (1.9±0.6)×10 -5 °K -1 (black circle in the figure), which is in agreement with the value reported for the linear thermal expansion coefficient of stainless steel. Thus, for measurement of this parameter with accuracy an adequate method should involve measurements for different material thicknesses following the above methodology.The above result confirms that of a previous reported work of Somer et al17 , where it was demonstrated that in the so-called Open Photoacoustic Cell (OPC) set-up, the actual value of the thermoelastic bending parameter (determined by the sample´s thermal expansion coefficient) approaches a constant value as the sample thickness becomes thicker, i.e. as the sample goes towards the ideal thermally thick regime (see Fig.…”
supporting
confidence: 93%
“…2,4,17,23 However, this model 22 breaks down for flexible materials, with strong thermoelastic bending, as is the case of Al and semi-transparent materials like glasses. 24,25,26 Recently, Sommer et al 27 found sizeable differences between Rousset et al 22…”
Section: And By Mcdonald Andmentioning
confidence: 97%
“…This drawback of the theoretical model was overcome with the introduction of an empirical power law to correlate the TD and TE components of the PA signal. Even though this method, 27 based on the measurement of the thermoelastic bending parameter (fitting parameter) as a function of the sample thickness, 4 yields reliable results for the Al thermal diffusivity, it may not retrieve the correct units of each PA signal.…”
Section: Theory and Their Experimental Data Obtained Formentioning
confidence: 99%
See 1 more Smart Citation
“…In the open-cell photoacoustic spectroscopy, the microphone with associated electronics and the lock-in amplifier Somer et al, 2013) play the major role in the experiments. A microphone is an acoustic-to-electric transducer that converts sound into an electrical signal.…”
Section: Introductionmentioning
confidence: 99%